Polityka ochrony praw konsumenta w Unii Europejskiej a wzrost jakości i konkurencyjności gospodarki - Jedlińska, Maja (The policy of consumer protection rights in the European Union vs. an increase of quality and competitiveness in economy, 2006)
Objective reasons weaken the position of a consumer in market economy. Such state of the matter is enhanced by marketing practices. Lack of activities towards slowing these processes down turns out to be destructive not only for a consumer, but also for the economy as a whole, which in turn is as strong as its weakest link, i.e. the consumer himself. The European Union has been working out standards regarding consumer protection for a long time. At present the system of such direct and indirect protection is used. Much success has been accomplished, however, numerous issues are still awaiting solutions. This is true for the Strategy of Consumer Policy in the years 2002-2006, as well as outlines of new directives. Transatlantic cooperation has to be deepened and also the significance of sustainable consumption model improved. These guidelines become crucial for Poland, if we attempt at obtaining strong position in economy of the Community.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 282-297